2017
DOI: 10.4186/ej.2017.21.7.15
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Benefits of the Integrated Alternative Technologies of the Portland Cement Production: A Case Study in Thailand

Abstract: Abstract. Under the 20122050, the International Energy Agency (IEA) and the World Business Council for Sustainable Development (WBCSD) have developed a roadmap for the reduction of energy and carbon intensities in cement production. The aim of this research is to study and evaluate the energy consumption (EN), global warming potential (GWP) impact, and economic assessment of Portland cement production. It was found that the total EN and GWP of conventional process were 3.29 GJ per ton of Portland cement and 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…The resistance to water uptake and acid degradation afforded by PCS 80 suggested that it might endow PCS 80 ‐impregnated Portland cement with similarly improved resilience. Treatment of Portland cement with sustainable additives that may increase its operational lifetime is an important goal, especially given that nearly a kilogram of CO 2 greenhouse gas emission results from production of each kilogram of Portland cement, accounting for 5–7% of global CO 2 emissions . A block of previously cured Portland cement was thus impregnated by submerging it in molten PCS 80 in vacuo, whereby the Portland cement took up 18.6 wt% of PCS 80 into its pores.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The resistance to water uptake and acid degradation afforded by PCS 80 suggested that it might endow PCS 80 ‐impregnated Portland cement with similarly improved resilience. Treatment of Portland cement with sustainable additives that may increase its operational lifetime is an important goal, especially given that nearly a kilogram of CO 2 greenhouse gas emission results from production of each kilogram of Portland cement, accounting for 5–7% of global CO 2 emissions . A block of previously cured Portland cement was thus impregnated by submerging it in molten PCS 80 in vacuo, whereby the Portland cement took up 18.6 wt% of PCS 80 into its pores.…”
Section: Methodsmentioning
confidence: 99%
“…[22] A block of previously cured Portland cement was thus impregnated by submerging it in molten PCS 80 in vacuo, whereby the Portland cement took up 18.6 wt% of PCS 80 into its pores. Treatment of Portland cement with sustainable additives that may increase its operational lifetime is an important goal, especially given that nearly a kilogram of CO 2 greenhouse gas emission results from production of each kilogram of Portland cement, accounting for 5-7% of global CO 2 emissions.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a heat audit at a cement plant is conducted to identify opportunities for decreasing heat consumption, increasing the productivity and improving the production has been carried out [3]. The heat consumption assessment of Portland cement production in a Thailand's cement plant was also reported and found 3.29 GJ per ton of cement [4]. Based on the audit results, there are several methods to improve heat conservation in cement plants: improving the quality of kiln feed in the kiln, modifying the preheater cyclone, repairing the control system, utilizing waste heat and improving the combustion process at the kiln [5].…”
Section: Introductionmentioning
confidence: 99%
“…The consequent lack of real data impacts negatively on the understanding and optimization of the system, which accounts for a major fraction of the plant heat losses [4]. Nevertheless, process optimization is a key target for the global cement industry, which is facing constantly increasing coal prices and always more demanding environmental regulations [5,6]. Numerical models could represent effective tools for filling the knowledge gap: indeed, their comprehensive predictions could constitute the theoretical support for new indirect monitoring approaches based on soft sensing [7], as well as optimization-oriented control strategies [8].…”
Section: Introductionmentioning
confidence: 99%